EFFECT OF EDUCATION INCOME LEVELS AND PARENTING PATTERNS ON CHILDREN’S SOCIAL BEHAVIOR - Putri, Hadisa; Suriansyah, Ahmad; Wahdini, Erny (Journal of K6, Education and Management, 2019)
The purpose of this study is to describe the influence: income level, level of education with parenting, income level, education level with children's social behavior, parenting parents with children's social behavior, income level, level of education with children's social behavior through parenting old. Descriptive quantitative research methods and path analysis. The sample of the study was 257 children 5-6 years in 11 TK Sambas District, West Kalimantan, cluster sampling was chosen using the Slovin formula from a population of 684 children in the Kindergarten of Sambas District, West Kalimantan. Data collection uses questionnaires, documentation and observation. The results showed that income levels influence parenting style, education level influences parents' parenting style, income level influences children's social behavior, education level influences children's social behavior, parenting parents influence children's social behavior, parenting parents are an intermediary influence the level of income on children's social behavior and level of education on children's social behavior.